2010
DOI: 10.1002/mame.201000148
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conducting Polypyrrole/Cellulose Nanocomposite Films with Enhanced Mechanical Properties

Abstract: PPy was synthesised by oxidative chemical polymerisation using xylan, CMC and NFC as additives. Conducting nanocomposite films were cast from aqueous slurries using doped PPy particles, CMC and NFC as the conducting and reinforcing phase, respectively. NFC‐based composites had higher conductivity and lower mechanical properties than CMC‐based homologues. SEM analysis showed that in PPy/NFC composites, PPy and NFC were arranged in two entangled networks, whereas, in PPy/NFC composites, CMC formed a continuous m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 40 publications
1
45
0
Order By: Relevance
“…[17][18][19][20][21][22][23][24][25][26] Recently, electroactive Ppy/chitosan (CS) composite nanospheres and highly conductive Ppy/cellulose nanocomposite films with enhanced mechanical properties were introduced. 27,28 CS as a biodegradable, biocompatible, nontoxic, and lowcost biopolymer was used to prepare Ppy/CS composite films with the aim of increasing the mechanical, 29 antibacterial, 30 electrochemical, 31 and biocompatible properties of the resulting products. 32 Also, its unique properties allow rapid blood clotting or transdermal drug delivery.…”
mentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26] Recently, electroactive Ppy/chitosan (CS) composite nanospheres and highly conductive Ppy/cellulose nanocomposite films with enhanced mechanical properties were introduced. 27,28 CS as a biodegradable, biocompatible, nontoxic, and lowcost biopolymer was used to prepare Ppy/CS composite films with the aim of increasing the mechanical, 29 antibacterial, 30 electrochemical, 31 and biocompatible properties of the resulting products. 32 Also, its unique properties allow rapid blood clotting or transdermal drug delivery.…”
mentioning
confidence: 99%
“…In a recent work, a first suggestion of xylan as additive for pyrrole polymerisation was given by our research group (Sasso et al 2010). Moreover, in the same work, it was demonstrated that NFC would slightly interfere with the percolation of PPy particles in the film, thus leading to PPy/NFC self standing films with outstanding conductivities (Sasso et al 2010).…”
Section: Introductionmentioning
confidence: 93%
“…Actually, the efficiency of other wood derivatives, such as carboxymethyl cellulose (CMC) and lignosulfonates in improving PPy electric conductivity (Sasso et al 2008;Yang and Liu 2009) and cellulose and nanofibrillated cellulose (NFC) in conferring film forming properties to conducting PPy/cellulose-based composites have been recently demonstrated (Sasso et al 2010(Sasso et al , 2011Rußler et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Sasso et al polymerized polypyrrole (PPy) in different mixtures of carboxymethyl cellulose (CMC), xylan (hemicellulose) and NFC to manufacture conductive nanocomposite films. [73] They observed that the films containing NFC had larger PPy particles which formed networks between the fibrils. Nanocomposites with CMC had two orders of magnitude lower conductivity compared to NFC which was attributed to insulating phases of CMC forming around the PPy particles.…”
Section: Paper Electronicsmentioning
confidence: 99%
“…[71][72] Conductive polymers can be composited with paper either by adding it in the form of a liquid suspension or by direct polymerization onto the cellulose fibers in solution or on paper. [73][74][75][76] It has been demonstrated that the type of cellulose and the surface charge of the fibers have a strong influence on the quality of the polymer coating on paper and hence the conductivity. Qian et al investigated the influence of the pulp type on the polymerization of polyaniline (PANI) on cellulose fibers.…”
Section: Paper Electronicsmentioning
confidence: 99%